Preparation method of fiber self-reinforced flame-retardant aerogel for building based on waste polyester / cotton textiles
By loosening, carding, needle-punching and ionic liquid dissolution treatment of waste slurry/cotton textiles, combined with freezing and shaping of aqueous ammonium polyphosphate solution, fiber self-reinforced flame retardant agel is formed, which solves the cellulose gas in recycling and reuse of waste textiles The problem of poor mechanical properties and flame retardant properties of the gel improves the porosity and heat resistance of the aerogel.
Patent Information
- Application Number
- CN202411313813.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the recycling and reuse method for waste polyester/cotton textiles has problems such as fiber strength loss, incomplete separation, high cost, and poor mechanical properties and flame retardant properties of cellulose aerogels.
By loosening, combing and needle-punching waste polyester/cotton textiles, dissolving cellulose with ionic liquid, freezing and freeze-drying combined with aqueous ammonium polyphosphate solution, fiber self-reinforced flame retardant agel is formed, and polyester needle-punching felt is used to form a fiber self-reinforced fire-retardant agel. As a support structure, the mechanical properties and flame retardant properties of the aerogel are improved.
The mechanical properties and flame retardant properties of cellulose aerogels are improved, the porosity and heat resistance of aerogels are improved, and the defects of poor mechanical properties and flame retardant properties of waste textile recycling are solved.
Smart Images

Figure CN119119568A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile preparation, in particular to a method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles. Background Art
[0002] As the global population increases, the textile industry develops rapidly, resulting in the generation of a large amount of waste textiles. Among the millions of tons of textile waste generated each year, most are polyester / cotton textiles. Compared with pure textiles, blended fabrics are more difficult to recycle and reuse. The traditional treatment methods are mainly incineration and landfill, which will have a great impact on the environment. At present, waste polyester / cotton fabrics are usually recycled and reused by mechanical opening, physical or chemical separation, but these methods all have certain problems. Mechanical opening will cause fiber strength loss and reduce product added value; physical or chemical separation methods often do not separate completely and are costly; in terms of physical separation and recovery, different solvents are usually used to dissolve the cotton fibers or polyester fibers in polyester / cotton blended fabrics, and then the undissolved solid part is filtered out, and then the filtrate and filter residue, i.e. the polyester and cotton components, are reused separately, but the current dissolution method is difficult to fully dissolve and completely separate, and the use of a large amount of solvents will cause excessively high processing costs; in terms of chemical separation and regeneration, it is still mainly in the laboratory stage, such as using biological fermentation, acid hydrolysis, etc. to decompose the cotton component in polyester / cotton fabrics to obtain polyester components.
[0003] The main component of cotton in waste polyester / cotton textiles is cellulose. At present, cellulose aerogel prepared with cellulose as raw material not only has the advantages of traditional aerogel such as high specific surface area, high porosity, and low density, but also has the characteristics of being renewable, degradable, and having good biocompatibility; however, cellulose aerogel also has some disadvantages, such as poor resilience, poor mechanical properties, and easy burning, which will also hinder its practical application areas.
[0004] Therefore, it is necessary to improve the waste blended fabric recycling method in the prior art to solve the above problems. Summary of the invention
[0005] The present invention overcomes the shortcomings of the prior art and provides a method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles, aiming to solve the defects of poor mechanical properties and poor flame retardant properties of aerogels obtained by recycling waste textiles.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles, comprising the following steps:
[0007] S1: opening, combing and needling waste polyester / cotton textiles in sequence to obtain waste polyester / cotton needle-punched felt;
[0008] S2: dissolving the waste polyester / cotton needle felt using an ionic liquid to obtain a cellulose solution and a polyester needle felt;
[0009] S3: placing the polyester needle felt in the cellulose solution and freezing it to shape it, and replacing it with an ammonium polyphosphate aqueous solution as a coagulation bath to obtain a flame-retardant cellulose / polyester composite hydrogel;
[0010] S4: freeze-drying the flame-retardant cellulose / polyester composite hydrogel to obtain a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles.
[0011] In a preferred embodiment of the present invention, the steps of opening, combing and needling the waste polyester / cotton textiles in S1 are specifically as follows:
[0012] S11: using a cloth opening machine to open the waste polyester / cotton textiles into waste polyester / cotton mixed fibers;
[0013] S12: treating the waste polyester / cotton mixed fibers with a dilute inorganic acid for 0.5-3 hours, washing and drying the acid-treated waste polyester / cotton mixed fibers to obtain acid-treated waste polyester / cotton mixed fibers;
[0014] S13: combing the acid-treated waste polyester / cotton mixed fibers into a fiber web, stacking the fiber web in a cross-lapping manner, and then feeding the fiber web into a needle punching machine for pre-needling and main needling, so as to obtain a relatively fluffy waste polyester / cotton needle punched felt through needling.
[0015] In a preferred embodiment of the present invention, in S12, the dilute inorganic acid is one of sulfuric acid, nitric acid and hydrochloric acid, the concentration of the dilute inorganic acid is 0.1-1wt%, and the dilute inorganic acid treatment temperature is 50-90°C.
[0016] In a preferred embodiment of the present invention, in S13, the cotton content in the fiber web is greater than 40%, and the needle punching machine parameters are: the needle punching density is 8-60 needles / cm 2 The pre-acupuncture depth is 11-16 mm, and the main acupuncture depth is 6-9 mm.
[0017] In a preferred embodiment of the present invention, the ionic liquid in S2 is 1-butyl-3-methylimidazolium chloride, and the dissolution conditions are: dissolving in an oil bath environment at 70-100° C. for 1-6 hours.
[0018] In a preferred embodiment of the present invention, the cellulose concentration in S2 is 0.5-10 wt %.
[0019] In a preferred embodiment of the present invention, the ammonium polyphosphate aqueous solution in S3 contains a cross-linking agent, the cross-linking agent is methyltrimethoxysilane, and the content of the cross-linking agent is 0.5-3wt% of the cellulose solution.
[0020] In a preferred embodiment of the present invention, the freezing and shaping temperature in S3 is -85 to -10°C, and the freezing and shaping time is 5 to 12 hours.
[0021] In a preferred embodiment of the present invention, the concentration of the ammonium polyphosphate aqueous solution in S3 is 1-3.5wt%, and the replacement time is 1-4 days.
[0022] In a preferred embodiment of the present invention, the freeze-drying treatment temperature in S4 is: -85 to -60°C, and the freeze-drying time is 36 to 48 hours.
[0023] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0024] (1) The present invention provides a method for preparing a fiber self-reinforced flame-retardant aerogel for construction based on waste polyester / cotton textiles. After the waste polyester / cotton textiles are loosened, combed and needled into needled felt, the cotton is directly dissolved as a cellulose solution, and the polyester needled felt is left as a supporting structure. After freeze-drying, a fiber self-reinforced aerogel is formed. Compared with the waste blended fabric recycling method in the prior art, the polyester and cotton in the waste polyester-cotton blended fabric are used together, and the polyester needled felt is used as a supporting structure, thereby improving the mechanical properties of the cellulose aerogel and solving the problem that the mechanical properties of the aerogel obtained by recycling waste textiles are poor.
[0025] (2) In the present invention, 1-butyl-3-methylimidazolium chloride is used as an ionic liquid to dissolve waste polyester / cotton needle felt, so that the cotton cellulose in the waste polyester / cotton needle felt can be dissolved into a cellulose solution. Compared with the prior art, the rate of cellulose dissolution can be promoted, the microstructure of cellulose can be adjusted, the porosity of the prepared aerogel can be increased, and the thermal resistance of the aerogel can be increased.
[0026] (3) In the present invention, the ammonium polyphosphate aqueous solution is replaced as a coagulation bath, and the polyester needle felt is made into a flame-retardant cellulose / polyester composite hydrogel. The ammonium polyphosphate can form a protective layer on the surface of the aerogel and can be thermally decomposed to form a carbon layer with the cellulose fibers. Compared with the prior art, it can block heat. In addition, the ammonium polyphosphate may affect the formation of pores during the gelation process, thereby increasing the porosity of the aerogel, and can improve the heat resistance of the aerogel, thereby ensuring the heat resistance of the aerogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 is a method step diagram of a preferred embodiment of the present invention; Figure 2 is an electron microscope image of an aerogel in a preferred embodiment of the present invention; Figure 3 This is an infrared thermal imaging image of a preferred embodiment of the present invention under a 60°C heating table; Figure 4 It is a combustion process diagram of the first embodiment of the preferred embodiment of the present invention in the outer flame of an alcohol lamp; Figure 5 It is a combustion process diagram of comparative example 1 of the preferred embodiment of the present invention in the outer flame of an alcohol lamp. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0031] like Figure 1 As shown, a method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles comprises the following steps:
[0032] S1: opening, combing and needling waste polyester / cotton textiles in sequence to obtain waste polyester / cotton needle-punched felt;
[0033] S2: dissolving the waste polyester / cotton needle felt using an ionic liquid to obtain a cellulose solution and polyester needle felt;
[0034] S3: placing the polyester needle felt in a cellulose solution and freezing it to shape it, and replacing it with an ammonium polyphosphate aqueous solution as a coagulation bath to obtain a flame-retardant cellulose / polyester composite hydrogel;
[0035] S4: The flame-retardant cellulose / polyester composite hydrogel is freeze-dried to obtain a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles.
[0036] After the waste polyester / cotton textiles are loosened, combed and needled into needle felt, the cotton is directly dissolved as a cellulose solution, and the polyester needle felt is left as a supporting structure. After freeze-drying, a fiber self-reinforced aerogel is formed. The polyester and cotton in the waste polyester-cotton blended fabric are used together, and the polyester needle felt is used as a supporting structure, which improves the mechanical properties of the cellulose aerogel and solves the defect of poor mechanical properties of the aerogel made by recycling waste textiles.
[0037] The specific steps of opening, combing and needling the waste polyester / cotton textiles in S1 are:
[0038] S11: using a cloth opening machine to open the waste polyester / cotton textiles into waste polyester / cotton mixed fibers; the opening step makes the waste textiles become loose fibers, which is convenient for subsequent carding and needle punching.
[0039] S12: treating the waste polyester / cotton mixed fibers with a dilute inorganic acid for 0.5-3h, washing and drying the acid-treated waste polyester / cotton mixed fibers to obtain acid-treated waste polyester / cotton mixed fibers; the dilute inorganic acid treatment can reduce the polymerization degree of cotton fibers in the waste polyester / cotton mixed fibers, thereby facilitating the subsequent dissolution of cotton cellulose.
[0040] In S12, the dilute mineral acid is one of sulfuric acid, nitric acid and hydrochloric acid, the concentration of the dilute mineral acid is 0.1-1wt%, and the dilute mineral acid treatment temperature is 50-90°C. The dilute acid treatment can partially hydrolyze certain chemical bonds in the fiber, improve the softness and spinnability of the fiber, and help improve the uniformity and strength of the fiber web. By accurately controlling the concentration, treatment time and treatment temperature of the dilute mineral acid, fiber damage can be avoided and recycling efficiency can be ensured.
[0041] S13: The acid-treated waste polyester / cotton mixed fibers are combed into a fiber web, and the fiber web is then stacked in a cross-lapping manner and sent to a needle punching machine for pre-needling and main needling, and a relatively fluffy waste polyester / cotton needle punched felt is obtained by needling. The combing step can make the fiber web more uniform, and the cross-lapping and needling treatment increase the fluffiness and thickness of the fiber web, which helps the final product have better thermal insulation performance. The needling process can fix the fiber position, increase the entanglement and adhesion between fibers, and thus improve the mechanical strength and stability of the final product.
[0042] In S13, the cotton content in the fiber web is greater than 40%, and the needle punching machine parameters are: the needle punching density is 8-60 needles / cm 2, the pre-needling depth is 11-16mm, and the main needling depth is 6-9mm. Ensure that the fiber web is fully entangled and fixed during the needling process, while avoiding excessive damage to the fiber, and help control the fluffiness of the fiber web, so that it has a certain thickness and maintains softness.
[0043] The ionic liquid in S2 is 1-butyl-3-methylimidazolium chloride, and the dissolution conditions are: dissolving in an oil bath environment at 70-100°C for 1-6 hours. 1-Butyl-3-methylimidazolium chloride is an effective solvent that can efficiently dissolve cellulose, which helps to convert cellulose in waste polyester / cotton textiles into cellulose solution. The dissolution effect of the ionic liquid helps to adjust the microstructure of cellulose, thereby affecting the pore structure and thermal insulation properties of the final aerogel.
[0044] The cellulose concentration in S2 is 0.5-10 wt%. The cellulose solution will be combined with the polyester needle felt. The proper adjustment of the cellulose concentration is conducive to the formation of a uniform composite hydrogel, and can adjust the pore structure of the cellulose aerogel to improve the mechanical properties of the cellulose aerogel.
[0045] The ammonium polyphosphate aqueous solution in S3 contains a crosslinking agent, which is methyltrimethoxysilane, and the content of the crosslinking agent is 0.5-3wt% of the cellulose solution. Methyltrimethoxysilane, as an effective crosslinking agent, can react with hydroxyl groups in cellulose molecules to form a stable chemical crosslinking network, thereby improving the mechanical strength and stability of the hydrogel. Ammonium polyphosphate itself has a flame retardant effect, and the crosslinking network formed by methyltrimethoxysilane can further improve the flame retardant properties of the material.
[0046] The freezing setting temperature in S3 is -85 to -10°C, and the freezing setting time is 5-12 hours. Low-temperature freezing helps to enhance the structural stability of the hydrogel and reduce deformation and cracking during subsequent processing. During the freezing setting process, the formation and growth of ice crystals will affect the pore structure of the gel. By controlling the freezing temperature and time, the size and distribution of the pores can be adjusted to ensure the porosity and thermal conductivity of the final aerogel.
[0047] The concentration of the ammonium polyphosphate aqueous solution in S3 is 1-3.5wt%, and the replacement time is 1-4 days. The extension of the replacement time can ensure that the ammonium polyphosphate fully reacts with the cellulose to form a uniform hydrogel and avoid local gelation that is too fast or too slow. The solvent in the cellulose solution is replaced by a 1wt% ammonium polyphosphate aqueous solution. This process is usually intended to allow the cellulose molecules to form a stable three-dimensional network structure in the absence of a solvent, thereby obtaining a hydrogel. Ammonium polyphosphate is a commonly used flame retardant, which not only serves as a coagulation bath during the replacement process, but also forms a cross-linked structure with cellulose, thereby enhancing the flame retardant properties of the cellulose gel. At the same time, the addition of methyltrimethoxysilane helps to improve the thermal stability and mechanical properties of the cellulose gel.
[0048] The freeze-drying treatment temperature in S4 is: -85~-60℃, and the freeze-drying time is 36-48h. At a lower freeze-drying temperature, the water in the hydrogel is frozen into ice crystals, avoiding the structural collapse caused by water evaporation during the drying process. During the freeze-drying process, the sublimation of ice crystals can form a uniform pore structure. By controlling the temperature and time of freeze-drying, the porosity of the aerogel can be optimized, thereby improving its thermal insulation properties. The pore structure formed during the freeze-drying process helps to improve the mechanical properties of the aerogel, such as compressive strength and flexural strength.
[0049] Depend on Figure 2 It was concluded that the undissolved polyester fibers were evenly dispersed in the cellulose aerogel, and the entire structure was a porous structure. This porous structure could effectively scatter and slow down heat conduction, which was beneficial to the thermal insulation performance of the fiber self-reinforced flame-retardant gas aerogel.
[0050] Depend on Figure 3 It was concluded that after a certain period of heating, the temperature of the aerogel increased slowly, and the aerogel had the effect of thermal insulation.
[0051] Embodiment 1
[0052] This embodiment prepares a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles, and the method steps are as follows:
[0053] S1: opening, combing and needling the waste polyester / cotton textiles to form waste polyester / cotton needle-punched felt: removing the decorations on the waste polyester / cotton textiles, using a cloth opening machine to open the waste polyester / cotton textiles into waste polyester / cotton mixed fibers, and then treating the waste polyester / cotton mixed fibers with 0.5wt% sulfuric acid to reduce the polymerization degree of cotton fibers in the waste polyester / cotton mixed fibers for easy dissolution, and then washing with deionized water to neutrality and drying; finally, combing the waste polyester / cotton mixed fibers with a cotton content of 65% into a fiber web, and then stacking the fiber web in a cross-laying manner, and sending it to a needle loom for pre-needling and main needling, and the needling process parameters are: the needling density is 20 needles / cm 2The pre-acupuncture depth was 15 mm and the main acupuncture depth was 8 mm.
[0054] S2: The cotton component in the waste polyester / cotton needle felt is dissolved with 1-butyl-3-methylimidazole chloride to obtain a 2wt% cellulose solution, and methyltrimethoxysilane is added to facilitate subsequent cross-linking with the flame retardant ammonium polyphosphate. The amount of methyltrimethoxysilane added is 1.5wt% of the cellulose solution. The undissolved polyester needle felt is left in the cellulose solution as a supporting structure. After being frozen and fixed in an environment of -18°C for 10 hours, it is replaced with a 1wt% ammonium polyphosphate aqueous solution as a coagulation bath. The replacement time is 2 days, and the coagulation bath is replaced every day to obtain a flame-retardant cellulose / polyester composite hydrogel;
[0055] S3: The flame-retardant cellulose / polyester composite hydrogel is freeze-dried to obtain a fiber self-reinforced flame-retardant gas gel, the freeze-drying temperature is -85°C, and the freeze-drying time is 48 hours.
[0056] Embodiment 2
[0057] The second embodiment is exactly the same as the first embodiment, except that: in step S2, a 1.5 wt% ammonium polyphosphate aqueous solution is used as a coagulation bath for replacement.
[0058] Embodiment 3
[0059] Example 3 is exactly the same as Example 1, except that in step S2: 2 wt % ammonium polyphosphate aqueous solution is used as a coagulation bath for replacement.
[0060] Comparative Example 1
[0061] Comparative Example 1 is completely the same as Example 1, except that in step S2: methyltrimethoxysilane is not added, and deionized water is used as the coagulation bath for replacement.
[0062] Samples of the same specifications as in Examples 1 to 3 were taken, and the thermal conductivity, limiting oxygen index, and compressive strength of the samples were measured. The data of each sample are shown in Table 1:
[0063] Table 1 Thermal conductivity, limiting oxygen index, and compressive strength data of Examples 1 to 3 and Comparative Examples
[0064] Sample source Thermal conductivity (W / (m·k)) Limiting oxygen index % Compression strength(KPa) Embodiment 1 0.0385 28.5% 64.3 Embodiment 2 0.0396 29.1% 67.8 Embodiment 3 0.0403 30.2% 68.6
[0065] As shown in Table 1, with the increase of the concentration of the ammonium polyphosphate coagulation bath, the thermal conductivity of each sample shows an increasing trend, but the limiting oxygen index and compressive strength of the sample show an increasing trend. The compressive strength of Example 2 increases by 8.75% relative to Example 1, but Example 3 only increases by 1.47% relative to Example 2. In terms of comprehensive thermal conductivity, limiting oxygen index and compressive strength, Example 2 has better comprehensive performance.
[0066] Depend on Figure 4 and Figure 5 It can be seen that Example 1 stayed in the outer flame of the alcohol lamp for 12 seconds without burning, while Comparative Example 1 burned violently in the outer flame of the alcohol lamp for 4 seconds. The aerogel prepared in Example 1 has a flame retardant effect and can reduce the risk of fire during use.
[0067] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a fiber self-reinforced flame-retardant gel for construction based on waste polyester / cotton textiles, characterized in that: The following steps are involved: S1: opening, combing and needling waste polyester / cotton textiles in sequence to obtain waste polyester / cotton needle-punched felt; S2: dissolving the waste polyester / cotton needle felt using an ionic liquid to obtain a cellulose solution and a polyester needle felt; S3: placing the polyester needle felt in the cellulose solution and freezing it to shape it, and replacing it with an ammonium polyphosphate aqueous solution as a coagulation bath to obtain a flame-retardant cellulose / polyester composite hydrogel; S4: freeze-drying the flame-retardant cellulose / polyester composite hydrogel to obtain a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles.
2. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The steps of opening, combing and needling the waste polyester / cotton textiles in S1 are specifically as follows: S11: using a cloth opening machine to open the waste polyester / cotton textiles into waste polyester / cotton mixed fibers; S12: treating the waste polyester / cotton mixed fibers with a dilute inorganic acid for 0.5-3 hours, washing and drying the acid-treated waste polyester / cotton mixed fibers to obtain acid-treated waste polyester / cotton mixed fibers; S13: combing the acid-treated waste polyester / cotton mixed fibers into a fiber web, stacking the fiber web in a cross-lapping manner, and then feeding the fiber web into a needle punching machine for pre-needling and main needling, so as to obtain a relatively fluffy waste polyester / cotton needle punched felt through needling.
3. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 2, characterized in that: In S12, the dilute inorganic acid is one of sulfuric acid, nitric acid and hydrochloric acid, the concentration of the dilute inorganic acid is 0.1-1wt%, and the treatment temperature of the dilute inorganic acid is 50-90°C.
4. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 2, characterized in that: In S13, the cotton content in the fiber web is greater than 40%, and the parameters of the needle punching machine are: the needle punching density is 8-60 needles / cm 2 The pre-acupuncture depth is 11-16 mm, and the main acupuncture depth is 6-9 mm.
5. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The ionic liquid in S2 is 1-butyl-3-methylimidazolium chloride, and the dissolution conditions are: dissolving in an oil bath environment at 70-100° C. for 1-6 hours.
6. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The cellulose concentration in S2 is 0.5-10 wt %.
7. The method for preparing a fiber self-reinforced flame-retardant gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The ammonium polyphosphate aqueous solution in S3 contains a cross-linking agent, the cross-linking agent is methyltrimethoxysilane, and the content of the cross-linking agent is 0.5-3wt% of the cellulose solution.
8. The method for preparing a fiber self-reinforced flame-retardant gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The freezing setting temperature in S3 is -85 to -10°C, and the freezing setting time is 5 to 12 hours.
9. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The concentration of the ammonium polyphosphate aqueous solution in S3 is 1-3.5wt%, and the replacement time is 1-4 days.
10. The method for preparing a fiber self-reinforced flame-retardant gas gel for construction based on waste polyester / cotton textiles according to claim 1, characterized in that: The freeze drying treatment temperature in S4 is: -85 to -60°C, and the freeze drying time is 36 to 48 hours.
